Semicounductor devices: Physics and technology - SZE, S. M.; SZE, S. M. (New Delhi, Wiley India, 2002)
About the Book: Semiconductor Devices: Physics And Technology, 2nd Ed This book is an introduction to the physical principles of modern semiconductor devices and their advanced fabrication technology. It begins with a brief historical review of major devices and key technologies and is then divided into three sections: semiconductor material properties, physics of semiconductor devices and processing technology to fabricate these semiconductor devices. About The Author: S. M. Sze is UMC Chair Professor of the National Chiao Tung University and President of the National Nano Device Laboratories, Taiwan, R.O.C. For many years he was a member of the technical staff at Bell Laboratories
Include bibliographical references; Appendix A-B, 531-550p; Index 551-564p.